Immunogenicity and safety of the adjuvanted recombinant zoster vaccine in patients with solid tumors, vaccinated before or during chemotherapy: A randomized trial. Issue 8 (1st February 2019) - Vink, Peter; Delgado Mingorance, Ignacio; Maximiano Alonso, Constanza; Rubio‐Viqueira, Belen; Jung, Kyung Hae; Rodriguez Moreno, Juan Francisco; Grande, Enrique; Marrupe Gonzalez, David; Lowndes, Sarah; Puente, Javier; Kristeleit, Hartmut; Farrugia, David; et al.
Abstract : Background: The adjuvanted recombinant zoster vaccine (RZV) has demonstrated >90% efficacy against herpes zoster in adults ≥50 years of age and 68% efficacy in autologous hematopoietic stem cell transplant recipients ≥18 years of age. We report the immunogenicity and safety of RZV administered to patients with solid tumors (STs) before or at the start of a chemotherapy cycle. Method: In this phase 2/3 observer‐blind, multicenter study (NCT01798056), patients with STs who were ≥18 years of age were randomized (1:1) to receive 2 doses of RZV or placebo 1‐2 months apart and stratified (4:1) according to the timing of the first dose with respect to the start of a chemotherapy cycle (first vaccination 8‐30 days before the start or at the start [±1 day] of a chemotherapy cycle). Anti‐glycoprotein E (gE) antibody concentrations, gE‐specific CD4 + T cell frequencies, and vaccine response rates (VRRs) were assessed 1 month after dose 1 and 1 and 12 months after dose 2. Reactogenicity and safety were assessed in the total vaccinated cohort through 12 months after dose 2. Results: There were 232 participants in the total vaccinated cohort, 185 participants in the according‐to‐protocol cohort for humoral immunogenicity, and 58 participants in the according‐to‐protocol cohort for cell‐mediated immunogenicity. Postvaccination anti‐gE antibody concentrations, gE‐specific CD4 + T cell frequencies and VRRs were higher in RZV recipients than in placebo recipients. Solicited adverse events (AEs) were more frequent among RZV recipients than placebo recipients. Incidence of unsolicited AEs, serious AEs, fatalities, and potential immune‐mediated diseases were similar between RZV and placebo recipients. Conclusion: RZV was immunogenic in patients with STs receiving immunosuppressive chemotherapies. Humoral and cell‐mediated immune responses persisted 1 year after vaccination. No safety concerns were identified. Abstract : In patients with solid tumors treated with immunosuppressive chemotherapies, the adjuvanted recombinant zoster vaccine (RZV) was immunogenic and immunogenicity persisted through 1 year after vaccination. RZV was well tolerated, and no safety concerns were identified.